Analysis of Regional Own-Source Revenue, General Allocation Fund, Special Allocation Fund and Economic Growth on the Local Government Capital Expenditure - Stellamaris Metekohy; Donny Dharmawan; Ratnawita Ratnawita; Ida Harahap; Musran Munizu (Yayasan Riset dan Pengembangan Intelektual, 2024)
In comparison to other regional expenditures, the capital expenditure allocation in the West Nusa Tenggara Province District Budget remains relatively small. While capital expenditure fluctuates, it is allocated for public service such as facilities and infrastructure where West Nusa Tenggara Province district have growing populations. This purpose of this study is to determine the effects of Regional Own-Source Revenue, General Allocation Fund, Special Allocation Fund and Economic Growth on Capital Expenditure of Districts in West Nusa Tenggara Province in the 2017-2022 period partially and simultaneously. The quantitative approach and regression analysis are used in this study. The sampling technique uses the census method which is the method by taking population and the population used is 10 districts in NTB Province. The data analyzed by using SPSS 22 for the Windows. The results of this study showed that Regional Own-Source, General Allocation Fund and Economic Growth have a significant effect on Capital Expenditure, while the Special Allocation Fund has an insignificant effect on Local Government Capital Expenditure in NTB Province in the 2017-2022 period. The findings of this research can be reference for future researchers who will study similar problems. The study findings are also anticipated to give the government advice and knowledge about how crucial it is to maximize regional potential in order to raise the standard of public services and regional progress to the government.